Indentification of novel MSTO1 compound heterozygous mutations in a Chinese family with recessive cerebellar atrophy and ataxia - Chen, Jia; Xiao, Junfang; Chen, Ge; Xu, Qiang; Wu, Xingwu; Tian, Lifeng; Huang, Zhihui; Xin, Cailin; Zhao, Yan; Guo, Zhen; Zou, Yang; Wu, Qiongfang (Frontiers in Neurology, 2022)
MSTO1 is a nuclear-encoded cytoplasmic protein involved in mitochondrial fusion and distribution. Its disruption causes an extremely rare mitochondrial disorder characterized by early-onset myopathy and cerebellar ataxia. The genotype-phenotype correlation in MSTO1 gene is rarely studied before 2017, and only 23 mutations have been described in the patients. Here, we reported two siblings with progressive cerebellar atrophy and ataxia in a Chinese family. Two compound heterozygous mutations in the MSTO1 gene, a novel missense mutation c.571C>T (p.Arg191Trp) and a reported frameshift mutation c.1259delG (p.Gly420ValfsTer2), were identified in the patients by whole exome sequencing. Except for ataxia and delayed motor, both of the siblings also have low birth weights, learning difficulties, and dysarthria. Our report enriched the genotype and phenotype spectrums of the MSTO1 related disorder and supported the recessive inheritance of the disease.